Pelatihan Pembuatan Media Pembelajaran Berbasis Tutorial berbantuan Video bagi Guru - Sesriyani, Lodya; Prasetyawan, Enggar; Permana, Putut Said (Universitas Pamulang, 2023)
This PkM aims to provide training to teachers at SMPN 20 Dumai Dumai. SMPN 20 Dumai is an example of formal education. The school, which is located on Jalan Raya Tiangjong, has problems related to the learning process, namely the use of appropriate media according to the material and needs of students. In addition, the challenge that teachers feel the most is motivating students in learning. Video media is believed to be able to increase student motivation in learning. This is the background for this PkM activity, PkM will be conducted by 3 lecturers and involve 3 students. This activity will last for 3 days on March 20-22 2023. This activity will begin by observing the teacher's needs in providing learning materials. After making observations it was found that most of the teachers used simple activities in providing learning materials. The activity continued with conducting training on how to apply Tutorial-based learning media to learning at SMPN 20 Dumai. Keywords: Formal education, SMPN 20 Dumai, Tutorial-based learning media